In vivo effects of histone H3 depletion on nucleosome occupancy and position in Saccharomyces cerevisiae. - Andrea J Gossett; Jason D Lieb (PLoS Genetics, 2012)
Previous studies in Saccharomyces cerevisiae established that depletion of histone H4 results in the genome-wide transcriptional de-repression of hundreds of genes. To probe the mechanism of this transcriptional de-repression, we depleted nucleosomes in vivo by conditional repression of histone H3 transcription. We then measured the resulting changes in transcription by RNA-seq and in chromatin organization by MNase-seq. This experiment also bears on the degree to which trans-acting factors and DNA-encoded elements affect nucleosome position and occupancy in vivo. We identified ∼60,000 nucleosomes genome wide, and we classified ∼2,000 as having preferentially reduced occupancy following H3 depletion and ∼350 as being preferentially retained. We found that the in vivo influence of DNA sequences that favor or disfavor nucleosome occupancy increases following histone H3 depletion, demonstrating that nucleosome density contributes to moderating the influence of DNA sequence on nucleosome formation in vivo. To identify factors important for influencing nucleosome occupancy and position, we compared our data to 40 existing whole-genome data sets. Factors associated with promoters, such as histone acetylation and H2A.z incorporation, were enriched at sites of nucleosome loss. Nucleosome retention was linked to stabilizing marks such as H3K36me2. Notably, the chromatin remodeler Isw2 was uniquely associated with retained occupancy and altered positioning, consistent with Isw2 stabilizing histone-DNA contacts and centering nucleosomes on available DNA in vivo. RNA-seq revealed a greater number of de-repressed genes (∼2,500) than previous studies, and these genes exhibited reduced nucleosome occupancy in their promoters. In summary, we identify factors likely to influence nucleosome stability under normal growth conditions and the specific genomic locations at which they act. We find that DNA-encoded nucleosome stability and chromatin composition dictate which nucleosomes will be lost under conditions of limiting histone protein and that this, in turn, governs which genes are susceptible to a loss of regulatory fidelity.